2022
DOI: 10.3390/f13101618
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Morphological, Anatomical and Physiological Analyses Explain the Difference of Wounding-Induced Agarwood Formation between Ordinary Agarwood Nongrafted Plants and Five Grafted Qi-Nan Clones (Aquilaria sinensis)

Abstract: Agarwood is the dark resinous heartwood of injured ordinary Aquilaria sinensis (OA). Recently, some new clones of A. sinensis (Qi-Nan) that intensively produce high-quality agarwood were selected and cultivated by grafted clonal seedlings. However, very little is known about their agarwood formation mechanism, and it is unclear whether the current method of distinguishing Qi-Nan from OA by observing its leaf apparent morphology is scientifically reliable. In this study, the differences between OA and Qi-Nan cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The first change observed after tree injury is a decrease and disappearance of starch in parenchyma cells. The second change is the significant saponification in parenchymal tissue cells, resulting in the appearance of brown droplets ( Kono et al., 2019 ; Li et al., 2022 ). This study showed that the development of Qi-Nan agarwood consumed starch and soluble sugar in parenchyma cells, and the agarwood formed was filled in the xylem.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first change observed after tree injury is a decrease and disappearance of starch in parenchyma cells. The second change is the significant saponification in parenchymal tissue cells, resulting in the appearance of brown droplets ( Kono et al., 2019 ; Li et al., 2022 ). This study showed that the development of Qi-Nan agarwood consumed starch and soluble sugar in parenchyma cells, and the agarwood formed was filled in the xylem.…”
Section: Discussionmentioning
confidence: 99%
“…When the development of agarwood is induced, the tree body of A. sinensis is damaged, the balance of microecosystem is broken, and some endophytic fungi will grow rapidly, causing the defense response of agarwood tree body ( Liu Y. et al., 2022 ). The active cells in the xylem use starch and soluble sugar as metabolic substrates to produce a large number of secondary metabolites, including bioactive substances such as sesquiterpenes and chromones ( Li et al., 2022 ). Agarwood is formed and filled in the xylem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of Qi-Nan agarwood and the differences in composition between Qi-Nan agarwood and ordinary agarwood have attracted much attention [6,[10][11][12][13]. Unfortunately, there are few reports of Qi-Nan grafted seedlings.…”
Section: Introductionmentioning
confidence: 99%